Bone marrow adiposity is inversely associated with bone mineral density in postmenopausal females - Lejla Milišić; Sandra Vegar-Zubović; Amina Valjevac; Suada Hasanović-Vučković (Medicinski glasnik, 2019)
Aim: To evaluate vertebral bone marrow adiposity (BMA) using magnetic resonance spectroscopy (MRS) in postmenopausal women and to determine an association of bone density with bone marrow fat content. Methods: This cross-sectional study included 120 postmenopausal women referred for osteoporosis screening. All women underwent assessment of bone mineral density by dual X-ray absorptiometry (DXA), who were divided based on T scores into osteoporosis (OST; n=60) and control group (CG; n=60). MRS was used to measure fat fraction (FF), lipid/water ratio (LWR) and fat content (FC) at vertebral spine (L1-L4). Results: Mean age, menopause or reproductive period duration was not significantly different between women in OST and control group. Median LWR in OST group was significantly higher compared to CG, 31.5 (22.9-38.8) vs. 28.7 (13.7-37.3) (p=0.039). Median FC was significantly higher in OST compared to the control group, 47.0 (46.3-78.8) and 46.4 (44.3-48.6), respectively (p=0.011). FC was significantly negatively associated with BMD at lumbar spine (Rho=-0.042; p<0.001) and with BMD at hip (Rho=-0.64; p<0.001). In logistic regression model, FC remained independently associated with osteoporosis after controlling for confounders (age, menopause duration, reproductive period duration and body mass index) (OR=1.3; 95% CI 1.1-1.6). Conclusion: Bone marrow adiposity is an independent predictor of low bone mass in postmenopausal women suggesting its role as a therapeutic target in postmenopausal osteoporosis management.
Keywords: adiposity; magnetic resonance spectroscopy; osteoporosis